Generic Health-Related Quality of Life in Patients Seeking Care for Pelvic Organ Prolapse. Issue 6 (June 2021) - Bradley, Catherine S.; Brown, Heidi W.; Shippey, Stuart S.; Gutman, Robert E.; Andy, Uduak U.; Yurteri-Kaplan, Ladin A.; Kudish, Bela; Mehr, Allen; O'Boyle, Amy; Foster, Raymond T.; Anger, Jennifer T.; Ten Eyck, Patrick; et al.
Abstract : Objective: Using the American Urogynecologic Society multicenter Pelvic Floor Disorder Registry for Research, we (1) compared generic quality of life (QOL) in women planning pelvic organ prolapse (POP) treatment (surgery vs pessary), (2) correlated generic and condition-specific QOL scores, and (3) identified associations between generic QOL and other factors. Methods: This cross-sectional analysis assessed generic physical and mental QOL using the Patient-Reported Outcomes Measurement Information System Global Health Scale at baseline. Global Physical and Mental T-scores center on a representative US population sample (mean [SD], 50 [10]; higher scores, better health). Condition-specific QOL was assessed with Pelvic Floor Distress Inventory, Pelvic Floor Impact Questionnaire, and POP/Urinary Incontinence Sexual Function Questionnaire. Linear regression models identified associations between clinical factors and Global Physical/Mental scores. Results: Five hundred sixty-eight women (419 surgery, 149 pessary) were included. Surgery patients were younger, heavier, and more often sexually active (all P 's ⩽ 0.01). Global Physical scores were lower in the surgery versus pessary group, but not likely clinically meaningful (mean [SD], 48.8 [8.1] vs 50.4 [8.5]; P = 0.035); Global Mental scores were similar (51.4 [8.4] vs 51.9 [9.5], P = 0.56). Global Health scores correlated with Pelvic Floor Distress Inventory, Pelvic Floor Impact Questionnaire, and POP/Urinary Incontinence Sexual Function Questionnaire scores (all P 's < 0.0001). In multivariable models, menopause was associated with better physical QOL, and constipation, coronary artery disease, pelvic pain, and increased body mass index with worse physical QOL. Age was associated with better mental QOL, and constipation, fecal incontinence, pelvic pain, and coronary artery disease with worse mental QOL. Conclusions: Women choosing POP surgery versus pessary had similar physical and mental generic QOL. Abstract : Supplemental digital content is available in the text.